Culture and Economy - Димаджио, Пол (Journal of Economic Sociology, 2010)
The goal of the paper is to give the critical review of the studies devoted to the interaction between culture and economics. Most of us do not prejudice the sociological hypothesis that economic relations have particular impact on ideas, world-view and symbols. Much more rarely we hear that the opposite is also true: different cultural aspects shape economic institutions and processes this means that this line is more promising for economic sociology and interdisciplinary dialogues. That is why the author firstly considers the cultural influence on economy and only then the impact of economy on the culture. The paragraph on consumption is given in the text.